Effect of sex chromosome complement on sodium appetite and Fos-immunoreactivity induced by sodium depletion. - Dadam, F.M. (2014)
Effect of sex chromosome complement on sodium appetite and Fos-immunoreactivity induced by sodium depletion. Am J Physiol Regul Integr Comp Physiol 306: R175–R184, 2014. First published November 20, 2013; doi:10.1152/ajpregu.00447.2013.—Previous studies indicate a sex chromosome complement (SCC) effect on the angiotensin II-sexually dimorphic hypertensive and bradycardic baroreflex responses. We sought to evaluate whether SCC may differentially modulate sexually dimorphic-induced sodium appetite and specific brain activity due to physiological stimulation of the rennin angiotensin system. For this purpose, we used the “four core genotype” mouse model, in which the effect of gonadal sex and SCC is dissociated, allowing comparisons of sexually dimorphic traits between XX and XY females as well as in XX and XY males. Gonadectomized mice were sodium depleted by furosemide (50mg/kg) and low-sodium diet treatment; control groups were administered with vehicle and maintained on normal sodium diet. Twenty-one hours later, the mice were divided into two groups: one group was submitted to the water-2% NaCl choice intake test, while the other group was perfused and their brains subjected to the Fos-mmunoreactivity (FOS-ir) procedure. Sodium depletion, regardless of SCC (XX or XY), induced a significantly lower sodium and water intake in females than in males, confirming the existence in mice of sexual dimorphism in sodium appetite and the organizational envolvement of gonadal steroids. Moreover, our results demonstrate a SCC effect on induced brain FOS-ir, showing increased brain activity in XX-SCC mice at the paraventricular nucleus, nucleus of the solitary tract, and lateral parabrachial nucleus, as well as an XX-SCC augmented effect on sodium depletion-induced brain activity at two circumventricular organs, the subfornical organ and area postrema, nuclei closely involved in fluid and blood pressure homeostasis.